Challenges for maintaining surgical care practices in the COVID-19 pandemic: an integrative review - Ferreira, José Erivelton de Souza Maciel; Cavalcante, Tahissa Frota; Jansen, Raphaella Castro; Damasceno, Daniel Freitas Oliveira; de Oliveira, Lídia Rocha; da Silva, Maria Jocelane Nascimento; Rodrigues, Ana Paula (Investigación y Educación en Enfermería, 2023)
Objective: To present the knowledge produced on challenges of health services for maintaining surgical care practices in times of the COVID-19 pandemic. Methods: This is an integrative literature review, performed with descriptors ‘Operating rooms’ and ‘Coronavirus Infections’ in the MEDLINE/PubMed Central, IBECS, LILACS, BDENF, Coleta SUS, BIGG, BINACIS, SciELO, PubMed, Science Direct, and Cochrane Library databases. Results: Of the 405 studies analyzed, 27 met the inclusion criteria. The main challenges for surgical services during the pandemic were: (i) rearrangement of general practice in surgical units; (ii) administration and management of resources and elective surgeries; (iii) follow-up and control of preoperative patients to medium term; (iv) maintenance of patients’ and health professionals’ autonomy and mental health in this context; and (v) teaching health residents in the operating room. Conclusion: For surgical care services, the challenges caused by managing the high demand of patients in need of care resulted in the transfer of own resources to other units and the consequent hiring of professionals to meet the demand for these services due to the damming of postponed elective surgeries. This knowledge will allow us to propose strategies in decision making in this scenario, considering the new waves that may arise from this disease.